The value of shock index, modified shock index and age shock index to predict critical outcomes in a district level emergency centre - Aleka, Patrick (Department of Pathology, 2024)
Introduction Triage is the first and single most important step in patients' journey through an Emergency Centre (EC) and directly impacts the time to critical actions. Vital signs influence triage decisions, predict hospital admission and in-hospital mortality. The shock index (SI), modified shock index (MSI) and age shock index (ASI) are clinical markers derived from vital signs and correlate with tissue perfusion in critically ill patients. This study aimed to assess the value of SI, MSI and ASI to predict critical outcomes in all adult patients presenting to a district level emergency centre in South Africa. Methods This diagnostic study was performed as a retrospective observational study, using data from an existing electronic database at a district level hospital emergency centre over a period of 24 months. All adult patients who presented to Mitchells Plain Hospital were eligible for inclusion. Sensitivity, specificity and likelihood ratios were calculated for each variable as a predictor of critical outcomes with pre-determined thresholds. Results During the study period of 24 months, a total of 61 329 patients ≥ 18 years old presented to the EC with 60 599 included in the final sample. A red SATS triage category (+LR = 7.2) and SI ≥1.3 (+LR = 4.9) were the only two predictors of critical outcomes with any significant clinical value. The same two markers performed well for both patients with trauma and without trauma and specifically for patient who died while under the care of the emergency centre. Discussion The study demonstrated that patients with a SI≥1.3 have a significantly higher likelihood of having a critical outcome, whether the presenting complaint is trauma related or not, especially to predict mortality while under the care of the EC. Incorporating this marker as triage alerts could expedite the identification of patients with critical outcomes and improve patient throughput in the emergency centre.